Antibody‐mediated rejection due to anti‐HLA‐DQ antibody after pregnancy and delivery in a female kidney transplant recipient. (2nd July 2018) - Sagasaki, Makoto; Nakada, Yasuyuki; Yamamoto, Izumi; Kawabe, Mayuko; Yamakawa, Takafumi; Katsumata, Haruki; Mafune, Aki; Katsuma, Ai; Kobayashi, Akimitsu; Koike, Kentaro; Koike, Yusuke; Miki, Jun; et al.
ABSTRACT: Herein, we report a case of antibody‐mediated rejection (ABMR) due to anti‐HLA‐DQ antibody after pregnancy and delivery in a female kidney transplant recipient. A 34‐year‐old female recipient was admitted at 2 years after delivery for an examination of an elevated serum creatinine (S‐Cr) level. The patient had received a living kidney transplantation from her mother at 22 years of age, and her kidney graft function was almost stable. The episode biopsy showed peritubular capillaritis and transplant capillaropathy with C4d immunoreactivity in the peritubular capillaries. Additional examination revealed expression of a donor‐specific antibody (DSA) against HLA‐DQ5, leading to the diagnosis of chronic active ABMR. Intravenous immunoglobulin, plasma exchange, and rituximab were administered, and her S‐Cr level was maintained stable. This case demonstrates a possible relationship between pregnancy/delivery and development of ABMR due to a de novo DSA in a female kidney transplant recipient.